Rola władz regionalnych w stymulowaniu logistycznego rozwoju regionu na przykładzie włoskiego Regione Emilia Romagna - Nowak, Piotr (The Role of the Regional Authorities in Regional Logistic Development Stimulation on the Example of Italian Region Emilia Romagna, 2007)
The regional authorities are able to play an important role in the stimulation of regional logistic development. One of the best examples which confirms strongly such a statement is the concept implemented by Region Emilia Romagna (RER) in northern Italy. In the framework of the article this interesting approach of the logistics regional development stimulation is described. The crucial element of this approach is strong co-operation between regional and local authorities and regional enterprises. Such a model of the active approach in solving of logistic and transport problems can be an example for other regions which would like to create logistics policy as a tool for tackling problems caused by constantly increasing cargo flows.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 181-190